Lateral motion of a solid with a heterogeneous wettability surface driven by impacting droplets. (10th September 2022) - Zhang, Tongwei; Wu, Jie; Lin, Xingjian
Abstract: Abstract : When a droplet impacts a solid with a heterogeneous wettability surface, the generated asymmetric forces can manipulate the droplet, and its counterforces can also actuate the solid in theory. In this study, a water droplet impacting a movable hydrophobic substrate, which is decorated with a hydrophilic stripe and restrained by two linear dampers, is studied numerically. After preliminarily checking the effects of the solid mass and damping coefficient of linear dampers, the dynamic mechanisms of solid motion are explored by analysing the variations in the lateral force and instantaneous displacement distance of the solid. After that, the effects of the impact parameters on the solid lateral motion are mainly investigated, including the initial droplet diameter, impact velocity and offset distance between the impact point and hydrophilic stripe. On this basis, the reciprocating solid motion under successive droplet impacts is studied, and periodic motion with different amplitudes can be realized under appropriate impact conditions. The obtained results can shed some fresh insight into the potential applications of droplet–solid interactions, which are valuable for the collection and utilization of energy from natural environments.